The Influence Of Organizational Culture And Work Environment On Employee Loyalty Through Job Satisfaction As A Mediating Variable In The Government Environment City Of Cilegon - Dessy Hertantia; Basrowi Basrowi; RR. Andriani Sariwardani (Jurnal Economic Resource, 2026)
In the era of bureaucratic digitalization and public service transformation, the government is required to provide excellent and responsive services to meet public needs, particularly in the City Government of Cilegon. Issues related to organizational culture, work environment, and job satisfaction pose significant challenges that can influence employee loyalty. This study aims to empirically analyze the influence of organizational culture and work environment on employee loyalty through job satisfaction. This study is expected to provide theoretical and practical contributions to the development of human resource management policies in the public sector. The research method uses an explanatory quantitative approach, with a sample of 177 respondents from the City Secretariat and the Human Resources and Development Agency of Cilegon City. Data were collected through a closed-ended questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS. The results of the study indicate that organizational culture and work environment significantly influence job satisfaction and employee loyalty, both directly and indirectly through job satisfaction in the Cilegon City Government environment. In conclusion, organizational culture and work environment play a strategic role in enhancing employee loyalty within the Cilegon City Government. Enhancing loyalty cannot be achieved through partial measures but requires a holistic approach through strengthening organizational culture, creating a conducive work environment, and improving job satisfaction as a bridge to support the performance of local government organizations.